Novel “rich cloud” based data disaster recovery strategy - Fei XIANG; Chuan-yi LIU; Bin-xing FANG; Chun-lu WANG; GRui-ming ZHON (Tongxin xuebao)
Taking aim at the demand that on the basis of ensuring data reliability, the cloud provider wants to reduce its own data disaster recovery costs as much as possible, a method named RCDDRS (rich cloud based data disaster recovery strategy) was proposed, which can achieve a dynamic multi-objective schedulings. That means under the condition of the limited storage resources, the cloud provider chooses other cloud providers' resources to store data backup reasonably in order to lower the data disaster recovery costs and decrease the recovery time after the disaster. The simulation results show the feasibility and effectiveness of the proposed approach.